2016
DOI: 10.1007/s13197-016-2383-9
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and polyphenolic compound stability of lentil-orange peel powder blend in an extrusion process

Abstract: Lentil contains substantial amount of protein, carbohydrate, fibre and other nutrients and orange peels powder rich in carbohydrate and fiber content The present study was aimed to investigate the effects of extrusion processing parameter on the level of total phenolic content (TPC), total flavonoid content (TFC), total tannin content and antioxidant activity of lentil-orange peel powder blend, also to investigate the possibility of blend as a candidate for production of protein rich extruded product by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Citrus peels are by-products of juice extraction process and are treated as waste of little economic value by industry. However, they are important sources of antioxidants such as phenolic compounds (phenolic acids and flavonoids), which are important to human nutrition (Rathod & Annapure, 2017). Also, in the present study was observed that by increasing the ET levels, the TPC values were elevated.…”
Section: Total Phenolic Compounds (Tpc)supporting
confidence: 58%
See 1 more Smart Citation
“…Citrus peels are by-products of juice extraction process and are treated as waste of little economic value by industry. However, they are important sources of antioxidants such as phenolic compounds (phenolic acids and flavonoids), which are important to human nutrition (Rathod & Annapure, 2017). Also, in the present study was observed that by increasing the ET levels, the TPC values were elevated.…”
Section: Total Phenolic Compounds (Tpc)supporting
confidence: 58%
“…Currently, there is a high interest in the production of breakfast cereals through the combination of cereals with fruits and vegetables, since cereals are an important source of carbohydrates and proteins, while fruits and vegetables could provide some phytochemical compounds with important antioxidant potential (Gandhi & Singh, 2015). Among the materials that can be used to produce breakfast cereals are citrus fruits, which are an important source of antioxidant compounds, such as phenolic compounds and flavonoids (Rathod & Annapure, 2017). A citrus fruit of high importance in northwestern Mexico is the naranjita (Citrus mitis B.…”
Section: Introductionmentioning
confidence: 99%
“…Lentils are a good source of proteins and carbohydrates. The low glycaemic response and high fibre content of lentils help to control body weight by increasing the feeling of satiety (Rathod & Annapure 2017). Ciudad-Mulero et al (2018) used a Clextral EVOL HT32-H twin-screw extruder with co-rotating and intermeshing screws (SD 32 mm; L/SD ratio 24, 500 rpm, 50 kg h -1 ).…”
Section: Extrusion Based On Lentil Flourmentioning
confidence: 99%
“…The same tendency was previously observed by Ramos-Enríquez et al [48], who, by means of RSM showed that high temperatures increased the RSA of wheat bran. However, it was shown that the antioxidant activity of the lentil-orange (raw sample) was reduced from 95.6 to 60.6% by extrusion [49].…”
Section: Radical Scavenging Activitymentioning
confidence: 99%